Tumbuhan Ritual sebagai Arsip Hidup : Kajian Etnobotani dalam Tradisi Selamatan Desa Temas, Kota Batu - Fidellawati Wulandari; Diah Ayu Putri Susantia; Galuh Ajeng Ratri Anandita; Mohamad Rifki Yoshimi Hidayat; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
The Temas Village Selamatan tradition is closely related to the use of plants in its implementation, but the lack of documentation means that the ethnobotanical knowledge contained therein has not been widely revealed. This study aims to document and preserve local community knowledge regarding the use of ritual plants used in the Temas Village Selamatan tradition in Batu City. This study focuses on identifying plant types, habits, organs used, methods of use, stages of use, philosophical meanings, and conservation efforts. The type of research used is descriptive qualitative. Data was obtained through interviews, observation, and documentation. Key informants were determined using purposive sampling, then additional informants were selected using snowball sampling based on the recommendations of key informants. The data were analyzed using descriptive statistics to reinforce the presentation of the qualitative data obtained. The results showed that the dominance of plant use in rituals was based on the philosophical meaning contained in the plants, with the conservation status of the majority of plants classified as Not Evaluated according to the IUCN. The connection between plant use and the philosophical meaning contained therein indirectly supports plant conservation for the sustainability of rituals. These findings confirm that plants play a role as living archives that must be preserved for future generations.